A Conceptual View On Langhan Brihaniye Adhyaya of Charak Samhita - Sharma, Nippu Kumari; Biswas, Mainak; Bhople, Sonal Balkrishna; Joshi, Purva; Mishra, Satender Kumar (Journal of Neonatal Surgery, 2025)
Acharya Charaka has bestowed upon us a wealth of profound wisdom, among which the Langhanabrimhaniya Adhyaya stands out as a remarkable gem which describes the foundational principles of six major Ayurvedic therapeutic modalities — Langhana (lightening), Brimhana (nourishing), Rukshana (drying), Snehana (oleation), Swedana (sudation), and Stambhana (astringent/stabilizing). These interventions are core to balancing the dosas and treating a broad spectrum of diseases. The chapter begins with an emphasis on Langhana and Brimhana therapies to address conditions of excessive emaciation and corpulence as introduced in the preceding chapter. Through twelve critical questions and systematic explanations, Acharya Punarvasu highlights the significance of mastering these treatments as the mark of a true physician. Each therapy is defined by its action, indications, and pharmacological qualities of suitable substances thus offering a simplified yet comprehensive understanding. Ten types of Langhana are explained, ranging from purification procedures like Vamana and Virechana to lifestyle interventions such as fasting and exercise. Similarly, indications for Brimhana and Stambhana therapies are elaborated upon, outlining their relevance in various physiological and pathological states. The chapter concludes with the assertion that, despite the vast diversity in disease presentations and doshic interactions, all treatment modalities ultimately fall within the scope of these six foundational therapies — Shadvidha Chikitsa. Their correct application in accordance with individual constitution, disease condition, strength, season, and doshic imbalance is essential for effective and holistic healing in Ayurveda.